Investigating the correlation between self discipline, fieldwork, and work readiness: A study on vocational high schools - Ahmad Ridwan; Widiyanti Widiyanti; Didik Nurhadi (Universitas Papua, 2025)
The high unemployment rate among graduates of vocational high schools reflects a gap between educational outcomes and the demands of the industry. This study aims to examine the relationship between self-discipline and fieldwork practices on students’ readiness to enter the workforce. The research was conducted with 51 twelfth-grade students from the Mechanical Engineering program at Vocational High School “Sore” Tulungagung. The instruments used included a self-discipline scale, a student readiness scale, and fieldwork practice scores. Data were analysed using Pearson product-moment correlation. The findings revealed that self-discipline is positively and significantly correlated with students’ readiness to enter the workforce (r = 0.338; p < 0.05), while fieldwork practices also showed a significant positive correlation with student readiness (r = 0.415; p < 0.01). Simultaneously, both variables were significantly associated with students’ readiness (r = 0.471; p < 0.01). These results emphasise the importance of strengthening student discipline and providing relevant fieldwork experience in preparing vocational school graduates to be more competitive and adaptive in the evolving labour market. This study also offers practical implications for schools and industries in designing learning programs that are better aligned with workforce requirements.